International corporate social responsibility and post-entry performance of developing market INVs: The moderating role of corporate governance mechanisms - Zahoor, Nadia; Lew, Yong Kyu; Arslan, Ahmad; Christofi, Michael; Tarba, Shlomo Y. (My University, 2023)
Building on the stakeholder, agency, and resource dependence theories; this paper investigates the role of international corporate social responsibility (CSR) for the post-entry performance of developing market international new ventures (INVs) in the presence of corporate governance mechanisms to overcome their agency and environmental problems. We test and validate the conceptual model using survey data collected from 110 INVs operating in the developing market of Pakistan. Our results show that international CSR promotes the post-entry performance of developing market INVs. Further, we found that this association is moderated by corporate governance mechanisms of ownership, board independence, and returnee board members. Specifically, the relationship between international CSR and post-entry performance is weaker when ownership is concentrated but stronger when outsider and returnee board members are present in developing market INVs. The findings of this study have important theoretical and practical implications for INVs' social strategies and international performance contingent upon corporate governance.
Keywords: Corporate governance; Corporate social responsibility; Developing markets; International new ventures; Post-entry performance